The mortality burden of cachexia or weight loss in patients with colorectal or pancreatic cancer: A systematic literature review - Richard F. Dunne; Jeffrey Crawford; Karen E. Smoyer; Thomas D. McRae; Michelle I. Rossulek; James H. Revkin; Lisa C. Tarasenko; Philip D. Bonomi (Journal of Cachexia, Sarcopenia and Muscle, 2024)
Abstract Cancer‐associated cachexia is a multifactorial wasting disorder characterized by anorexia, unintentional weight loss (skeletal muscle mass with or without loss of fat mass), progressive functional impairment, and poor prognosis. This systematic literature review (SLR) examined the relationship between cachexia and survival in patients with colorectal or pancreatic cancer in recent literature. The SLR was conducted following PRISMA guidelines. Embase® and PubMed were searched to identify articles published in English between 1 January 2016 and 10 October 2021 reporting survival in adults with cancer and cachexia or at risk of cachexia, defined by international consensus (IC) diagnostic criteria or a broader definition of any weight loss. Included publications were studies in ≥100 patients with colorectal or pancreatic cancer. Thirteen publications in patients with colorectal cancer and 13 with pancreatic cancer met eligibility criteria. Included studies were observational and primarily from Europe and the United States. Eleven studies (42%) reported cachexia using IC criteria and 15 (58%) reported any weight loss. An association between survival and cachexia or weight loss was assessed across studies using multivariate (n = 23) or univariate (n = 3) analyses and within each study across multiple weight loss categories. Cachexia/weight loss was associated with a statistically significantly poorer survival in at least one weight loss category in 16 of 23 studies that used multivariate analyses and in 1 of 3 studies (33%) that used univariate analyses. Of the 17 studies demonstrating a significant association, 9 were in patients with colorectal cancer and 8 were in patients with pancreatic cancer. Cachexia or weight loss was associated with significantly poorer survival in patients with colorectal or pancreatic cancer in nearly two‐thirds of the studies. The classification of weight loss varied across and within studies (multiple categories were evaluated) and may have contributed to variability. Nonetheless, awareness of cachexia and routine assessment of weight change in clinical practice in patients with colorectal or pancreatic cancer could help inform prognosis and influence early disease management strategies.